ASPECTS OF INSOLVENCY IN CRIMINAL LAW - Kronis, Ivars (Administrative and Criminal Justice, 2015)
The article contains analysis of the legal norms that govern criminal liability for risks posed to insolvency. Based on case law and conclusions made by the law scholars, the preconditions have been studied the presence of which has to be proven in order to enable calling of a person to criminal account for leading to insolvency, filing of a fraudulent application for insolvency proceedings, hindering the insolvency proceedings and breach of the conditions of legal protection. The study enables deepen understanding of the preconditions to application of the law and helps to gain knowledge of criminal legal protection of insolvency and to avoid any behavior patterns that might be interpreted as criminal. The period since enactment of the new Insolvency Law that has changed the concept of insolvency as well as the course of procedure and therefore has affected the application of criminal legal protection has been too short for development of judiciary in this area. The few sources of scientific literature on the regulation of criminal legal protection of insolvency in the Criminal Law had been published before enactment of the new Insolvency Law. Five years of operation of the Insolvency Law is a kind of milestone for updating the issues of criminal legal protection of insolvency and extended assessment of the insolvency regulations in the Criminal Law.